Development of 1,5-Diaryl-Pyrazole-3-Formate Analogs as Antifungal Pesticides and Their Application in Controlling Peanut Stem Rot Disease - Ma, Yihui; Yang, Jun; Yang, Dangwei; Qin, Guangyu; Zu, Junhuai (Frontiers in Microbiology, 2022)
Stem rot disease caused by Sclerotium rolfsii is one of the destructive diseases in peanut and poses a big risk to peanut production. Current fungicides in the market have not provided satisfactory control efficacy and thus called for novel fungicides with different structure as an alternative treatment strategy. Our previously developed phenylpyrazole compound 3c demonstrated modest inhibitory effect against S. rolfsii. The following structure modification identified an unreported compound 6, which bears a 3-chloropyridinyl moiety as the most prominent derivative with an IC50 of 12 µg/ml in potato dextrose agar assay, higher than those of 0.8 and 1.8 µg/ml associated with thifluzamide and tebuconazole respectively. However, compound 6 showed similar controlling effects to those of thifluzamide and tebuconazole in field study. This conterbalance may be due to compound 6’s superior penetrating ability. This study underscores the potential of 1,5-diaryl-pyrazole-3-formate as an antifungal candidate for stem rot disease management.